Development of Socio-Scientific Issue (SSI)-Based Student Worksheets on Green Chemistry within the Gold Mining Context to Enhance Students' Attitude toward Environment - Fatchiyatun Ni'mah; Abudarin Abudarin; I Made Sadiana; Maya Mustika; Triliyansi Triliyansi; Adimetha Diraja Tangkasiang; Faisal Faisal (Jambura Journal of Educational Chemistry, 2026)
Global demands for more responsible and sustainable mining practices make understanding environmentally friendly gold mining operations increasingly crucial. This context is particularly relevant in Gunung Mas Regency, Central Kalimantan, where small-scale gold mining practices have triggered socio-economic dilemmas between financial gains for the community and serious risks to the environment (mercury pollution) and health. This issue highlights the need for educational interventions that can bridge the concepts of chemistry with real socio-scientific issues (SSI). This study aims to develop a feasible, practical, and effective SSI-based Student Worksheet for Green Chemistry topic. The research method used was Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The SSI-based Student Worksheet was developed to encourage active learning, critical thinking, and student team collaboration in investigating and solving mining problems. A purposive sampling technique was applied to select one out of six tenth grade science classes at MA N 1 Sepang. The selected class, consisting of 20 Tenth-Grade Science students, was involved in the evaluation process, assessing the effectiveness of the product after its implementation in the class. The findings demonstrated that the developed SSI-based worksheet was highly feasible (teacher assessment average of 3,60) and highly practical for classroom use (student response rate of 87,68%). Furthermore, descriptive analysis revealed a positive shift in students' affective domain, characterized by the complete elimination of the 'Not enough' environmental attitude category and an increase in the proportion of students reaching 'Good' categories. In conclusion, while the SSI-based student worksheet was proven to be highly feasible and highly practical tool for enhancing students’ attitude toward environment, its effect on students' long-term environmental attitudes remains relatively limited. This suggests that short-term interventions are insufficient to permanently change deep-rooted perspectives, and further comprehensive, long-term educational strategies are required.